Rethinking the Politics of Creativity: Posthumanism, Indigeneity, and Creativity Beyond the Western Anthropocene. (June 2022) - Henriksen, Danah; Creely, Edwin; Mehta, Rohit
With the emergence of Western posthuman understandings, new materialism, artificial intelligence (AI), and the growing acknowledgment of Indigenous epistemologies, an ongoing rethinking of existing assumptions and meanings about creativity is needed. The intersection of new technologies and philosophical stances that upend human-centered views of reality suggests that creativity is not an exclusively "human" activity. This opens new possibilities and assemblages for conceiving of creativity, but not without tensions. In this article, we connect multiple threads, to reimagine creativity in light of posthuman understandings and the possibilities for creative emergence beyond the Anthropocene. Creativity is implicated as emerging beyond non-human spaces, such as through digitality and AI or sources in the natural world. This unseats many understandings of creativity as positioned in Euro-Western literature. We offer four areas of concern for interrogating tensions in this area, aiming to open new possibilities for practice, research, and (re)conceptualization beyond Western understandings.